Perspectives on Arabic linguistics XXX papers from the annual symposia on Arabic Linguistics, Stony Brook, New York, 2016 and Norman, Oklahoma, 2017 - Khalfaoui, Amel; Tucker, Matthew A. (Studies in Arabic linguistics ;, 2019)
This volume contains selected papers from the Thirtieth Annual Symposium on Arabic Linguistics that was held at Stony Brook University in 2016, as well as two articles that are based on papers presented at the Thirty-First Annual Symposium on Arabic Linguistics, held at the University of Oklahoma in 2017. The chapters are theoretical and experimental explorations of a variety of linguistic topics and engage ideas ranging over three broad areas of research: phonetics and phonology, syntax, and experimental and computational linguistics. They deal with Classical and Modern Standard Arabic as well as a variety of dialects, including Iraqi, Egyptian, Moroccan, and Syrian Arabic.